Power Quality Assessment of Indoor LED Luminaires - Ayaz, Ramazan; Dogansahin, Kadir; Bozkurt, Altug; Kekezoglu, Bedri (IEEE, 2019)
Due to the fact that it is a semiconductor based lighting equipment, the LEDs have important effects on the power quality. In the ever-expanding lighting industry, the use of LED equipment is increasing day by day. Therefore, it is very important to analyze and interpret the effects of LEDs on the grid. In this study, power quality measurements of 4 different commercial LED luminaires have been realized and the results obtained have been interpreted. According to the measurements, it is found that the power factor values are acceptable for the luminaries when they are completely on. However, when the luminaries are dimmed, it has been observed that the power factor decreased and the current harmonics exceeded the limit values determined by the related standards. On the other hand, it is seen that all the luminaires provide flicker boundaries. As a result of the study, it has been concluded that the effects of dimmable equipment on power quality should be analyzed in more detail.
Keywords: LED lamps; power quality; harmonics; flicker; power factor; Automation & Control Systems; Energy & Fuels; Engineering